Ergonomics in an oral pathology laboratory: Back to basics in microscopy - Sundaragiri, Krishna Sireesha (Medknow Publications & Media Pvt Ltd, 2014)
Ergonomics is simply a science focused on “study of work” to reduce fatigue and discomfort through product design. A comprehensive ergonomics program for the pathology laboratory has become necessary to prevent the occurrence of work related musculoskeletal disorders (MSDs) and accidents. Most of the literature on ergonomics involve various web links or occasional studies on the effect of laboratory work and associated MSDs. A Google search was carried out corresponding to the terms “ergonomics”, “pathology laboratory”, “microscope”. All the relevant literature from web sources was sorted out and categorized. In this review, we intend to identify basic anthropometric factors, biomechanical risk factors, laboratory design considerations and specific microscopy-related considerations. The ultimate aim of ergonomics is to provide a safe environment for laboratory personnel to conduct their work and to allow maximum flexibility for safe research use.